Landscape Design: Putting Your Yard on Paper — Site Measurements and Base Maps - Gail Hansen; Erin Alvarez (EDIS)
ENH1166, a 5-page illustrated fact sheet by Gail Hansen and Erin Alvarez, discusses how to draw a base map using a legal site survey in order to plan a design for your yard’s landscape. Includes advice on taking measurements and tips for drawing a base map. Published by the UF Department of Environmental Horticulture, June 2010.